2015
DOI: 10.1155/2015/698425
|View full text |Cite
|
Sign up to set email alerts
|

Gastrojejunal Anastomosis Complications and Their Management after Laparoscopic Roux-en-Y Gastric Bypass

Abstract: Background. Complications at the gastrojejunal anastomosis after laparoscopic Roux-en-Y gastric bypass (LRYGB) are challenging in terms of diagnosis, therapy, and prevention. This study aims at identifying these complications and discussing their management. Methods. Data of 228 patients who underwent a LRYGB between October 2008 and December 2011 were reviewed retrospectively to evaluate the frequency and treatment of complications such as stenoses, marginal ulcers, perforated marginal ulcers, or anastomotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 25 publications
0
14
1
Order By: Relevance
“…Bariatric surgery with fast weight reduction resulted in good outcome in some of our patients [ 49 ]. However, this procedure should only be considered as a second-line therapy because of the high complication rate (incisional hernia, stenoses, ulcers, and nutrition deficiency) [ 50 , 51 ] and long treatment time including physical and psychological monitoring [ 52 ]. Carbonic anhydrase inhibitors, which reduce CSF secretion via inhibition of ions and water movement across the plexus choroid, are also used to manage IIH.…”
Section: Discussionmentioning
confidence: 99%
“…Bariatric surgery with fast weight reduction resulted in good outcome in some of our patients [ 49 ]. However, this procedure should only be considered as a second-line therapy because of the high complication rate (incisional hernia, stenoses, ulcers, and nutrition deficiency) [ 50 , 51 ] and long treatment time including physical and psychological monitoring [ 52 ]. Carbonic anhydrase inhibitors, which reduce CSF secretion via inhibition of ions and water movement across the plexus choroid, are also used to manage IIH.…”
Section: Discussionmentioning
confidence: 99%
“…The associated outcome and mortality after early reoperation is at the moment still at high rates, with incidence fluctuating between 13-60% (23,24,25,26). The distinction between late and early hemorrhage may have a decisive impact on the therapeutic management, early hemorrhage being in most studies reported to Hemoglobin serum levels before and after hemorrhage in every case (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…They are currently associated with low rates of postoperative complications (13). Hemorrhage from mechanical gastotrojejunal anastomosis represents a peculiar postoperative problem, with incidence fluctuating between 0,6% and 16%, being regularly self-limited (50% -70% of the cases) (22,23). Without perceiving it postoperatively or intraoperatively, due to poor haemostasis of the anastomotic suture lines, it can become life-threatening.…”
Section: Introductionmentioning
confidence: 99%
“…Even if marginal ulcers are multifactorial, the development of early marginal ulcer is more likely to be associated with local factors (ischemia, postoperative inflammation, stenosis, or foreign body) while late marginal ulcers are likely to be related to an increased acid exposition of the G-J anastomosis developing over time ( Fig. 5 ) [ 30 , 38 - 39 ]. Zollinger-Ellison syndrome also has to be ruled out.…”
Section: Staple-line Stenosis: Pathogenesis and Preventionmentioning
confidence: 99%